The Return of Tarzan - Burroughs, Edgar Rice, 1875-1950 (Salt Lake City, UT : Project Gutenberg, 1993)
"The Return of Tarzan" by Edgar Rice Burroughs is a novel first published in 1913. After sacrificing his chance to marry Jane Porter, Tarzan travels to Europe where he makes deadly enemies of the villains Rokoff and Paulovitch. His adventures lead him through France, Algeria, and eventually back to the African jungle of his youth. There, he becomes chief of the Waziri tribe and discovers the lost city of Opar. Meanwhile, Jane's yacht expedition along Africa's coast leads to unexpected reunions and life-threatening dangers in the wilderness. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Return_of_Tarzan
Release date is 1993-09-01
Judy Boss
Keywords: Tarzan (Fictitious character) -- Fiction; Fantasy fiction; Adventure stories